Corporate Social Responsibility, beyond the legal (GEON Journal (Management, Organizations and Business), 2016)
Corporate Social Responsibility CSR must seek continuous improvement, in turn generating added value for all its stakeholders, because it must go beyond legal requirements, must be voluntary and seek a balance between the social, economic and environmental impact generated by the organization (Cajiga). The elements that establish the concept of CSR do not express obedience to a specific type of organization, no matter their rationale, all have interest groups and dimensions that make the concept become a reality, such as economic, social and the ecological one is internal or external, this leads to each company establishing its own strategies and acting according to its context.In Colombia, the EPM group incorporated into its CSR system, a model to improve the relationship with interest groups, defined in a new political position vis-à-vis the territory, seeking to support regional development, based on two factors, to better understand the environment and the leadership for the establishment of rules of the game regarding the interest groups that act in the region, finding that the tendency to remedy existing problems predominates instead of establishing preventive and local development actions
Keywords: Corporate Social Responsability; Human Management; Management